2008
DOI: 10.4319/lo.2008.53.3.0890
|View full text |Cite
|
Sign up to set email alerts
|

Availability of iron from iron‐storage proteins to marine phytoplankton

Abstract: We examined the bioavailability of iron-storage proteins-including representatives of maxi-and miniferritins-to various species of marine phytoplankton. Both eukaryotic and prokaryotic species were able to grow rapidly with horse spleen ferritin (HoSF) or deoxyribonucleic acid (DNA)-binding proteins from starved cells (Dps) from Trichodesmium erythraeum as the sole Fe source in the medium. In the presence of ethylenediaminetetra-acetic acid (EDTA), cells grown with HoSF or Dps maintained exponential growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Biologically produced Fe-binding organic ligands are (i) related to alleviation of Fe stress [bacterially-produced siderophores (Rue and Bruland, 1995;Trick et al, 1995;Mawji et al, 2008;Velasquez et al, 2011), the toxin domoic acid produced by the diatom Nitzschia Maldonado et al, 2002)], (ii) retention of episodic iron input (Adly et al, 2015;Westrich et al, 2016), or (iii) ligands produced through biological recycling or basal biological activity such as hemes , ferritin (Castruita et al, 2008), polysaccharides (Ozturk et al, 2004;Hassler et al, 2011a), and EPS (Nichols et al, 2004;Hassler et al, 2011b;Norman et al, 2015). Interestingly, amongst most of these organic ligands, only EPS were reported to contribute to the pool of HS-like substances which is not surprising given that EPS and HS are polyfunctional macromolecules.…”
Section: Organic Ligands Distribution-sources Production and Loss Pmentioning
confidence: 99%
“…Biologically produced Fe-binding organic ligands are (i) related to alleviation of Fe stress [bacterially-produced siderophores (Rue and Bruland, 1995;Trick et al, 1995;Mawji et al, 2008;Velasquez et al, 2011), the toxin domoic acid produced by the diatom Nitzschia Maldonado et al, 2002)], (ii) retention of episodic iron input (Adly et al, 2015;Westrich et al, 2016), or (iii) ligands produced through biological recycling or basal biological activity such as hemes , ferritin (Castruita et al, 2008), polysaccharides (Ozturk et al, 2004;Hassler et al, 2011a), and EPS (Nichols et al, 2004;Hassler et al, 2011b;Norman et al, 2015). Interestingly, amongst most of these organic ligands, only EPS were reported to contribute to the pool of HS-like substances which is not surprising given that EPS and HS are polyfunctional macromolecules.…”
Section: Organic Ligands Distribution-sources Production and Loss Pmentioning
confidence: 99%
“…We performed a similar experiment with ferrihydrite sequestered in the iron-storage protein Dps (23). It has been shown that phytoplankton can take up Fe from Dps and that the uptake rate depends on the dissolution of the colloidal protein core that releases Fe (24). Our experimental results were slightly less noisy than those with ferrihydrite and showed no significant effect of pH on the kinetics of Fe uptake by T. weissflogii (P = 0.43, one-way ANOVA) (Fig.…”
Section: Reportsmentioning
confidence: 99%
“…Furthermore, complexation of remineralized Fe by EDTA would be expected to reduce Fe bioavailability. Indeed, Castruita et al (2008) found that growth rates of Thalassiosira weissflogii grown on Fe-ferritin complexes were reduced as EDTA was increased from 50 to 200 µmol l -1…”
Section: Bioavailability Of Remineralized Fementioning
confidence: 99%